Impact of Internet Banking on Customer Satisfaction in Private and Public Sector Banks - Srivastav, Garima; Mittal, Arun (Indian Journal of Marketing, 2016)
This is an exploratory research paper which discussed the impact of various Internet banking (IB) services on the overall satisfaction levels of the banking customers. With the help of forward stepwise regression, we explained how various variables both negatively and positively influenced customers’ satisfaction with Internet banking. Data were collected from 500 respondents (250 from private sector banks and 250 from public sector banks) in India (Delhi-NCR), constituting a 65% response rate. The application of this analysis revealed that customers wanted the private sector banks to improve upon the features like quality of service, frequency of reminder given for password change, safety, privacy of ID and password, and proper entering of the details in the bank registers. In case of the public sector banks, customers had different sets of concerns - like they were much worried about the lack of development in rules and regulation of E- banking as well as the poor regulatory framework in Internet banking. However, security issues aroused a common concern from the customers in case of both sectors of banks. The results also showed that the customers were ready to adopt Internet banking provided they were given necessary guidelines and constant built up of trust.